Use of Technology in Business Education: The Impact of the Internet, In-Class Use of Laptops, and the Cell Phones - (:unkn) unknown (INT MANAGEMENT DEVELOPMENT ASSOC-IMDA, 2011)
This study was designed to assess the role of technology in education. Students at an American university were sampled to obtain their general perceptions regarding technology in the classroom. The data was collected via an online survey during March/April 2011. Findings indicate that the students are increasingly using technology in their daily lives, ore very involved in social networks on the Internet, and they want their faculty to include more technology in the traditional classrooms. Other findings indicated that the laptop computers and cell phones in the classroom are detrimental and that measures should be taken to restrict their usage.